Genome-wide identification and expression analysis of IDD gene family in Gossypium hirsutum L - Shuo Zhang; Huixin Jiao; Dongyun Zuo; Qiaolian Wang; Limin Lv; Youping Zhang; Yi Yang; Guoli Song; Hailiang Cheng (Functional & Integrative Genomics, 2026)

Integrated ozone micro-nano bubbles and slurry ice precooling enhance broccoli preservation during shelf-life storage - Taishan Huang; Cheng Bian; Hongshan Lu; Junyan Shi; Zengting Xing; Shuzhi Yuan; Xiaozhen Yue; Jinhua Zuo; Xiangbin Xu; Xiaodi Xu; Qing Wang (Food Research International, 2026)

Climate- and runoff-driven interdecadal reorganization of large copepod communities in Laizhou Bay, Bohai Sea - Tao Zuo; Yongtao Li; Mingxiang Niu; Zhaolong Cheng; Jun Wang; Jianqiang Sun (Estuarine, Coastal and Shelf Science, 2026)

Process intensification of dilute methane abatement via a novel bidirectional tidal biofilter: Performance and mass-transfer mechanism - Heng Xu; Siyuan Shang; Quan Yuan; Zhiqiang Zuo; Jianbin Wang; Min Zheng; Zhenkang Wu; Xi Cheng; Huijiao Wang; Qi Qiu; Xinyu Zhang; Dawn E. Holmes (Chemical Engineering Journal, 2026)

Deep learning based pore detection of welded connection plates and its creep prediction - Shuohui Yin; Xinlong Cheng; Baoyin Zhu; Dongpeng Li; Dungui Zuo; Shuitao Gu; Gongye Zhang (Annals of Nuclear Energy, 2026)

Real-time hybrid shaking table test of a monopile offshore wind turbine under combined wind, wave–current, and seismic loading - Yanhui Zuo; Mengyu Li; Tianyi Gao; Zhongxing Wang; Cheng Li (Ocean Engineering, 2026)

Naturally occurring biopterin as a photosensitizer for enhanced photodegradation of sulfonamides in aquatic environments - Bing Li; Yu-Ze Han; Ye-Chao Tian; Xin Wang; Chi-Cheng Deng; Xiao-Ya Zhou; Shuo Zhang; Yan-Ting Zuo; Wen-Tao Li; Ai-Min Li (Environmental Pollution, 2026)

Effects of dietary yeast cell wall supplementation on growth performance, serum enzyme activity, and immune gene expression in Pacific white shrimp (Litopenaeus vannamei) - Chuan Chen; Xinhe Ruan; Jinhong Shan; Zijie Xuan; Huitao Cheng; Fengqi Huang; Lihua Li; Zongyang Li; Xiaoling Zuo; Jie Yu; Huihong Zhao (Animal Feed Science and Technology, 2026)

Biotransformation of Cimetidine by Chlamydomonas sp. SI-16: CYP450-Driven Detoxification and Immobilized Photobioreactor Validation - Kang Li; Jun Liu; Yongtao Cheng; Chenxi Zhou; Kang Shan; Chuanyue Peng; Wenjing Yan; Ying Liu; An Xu; Min Zuo (Journal of Hazardous Materials, 2026)

Structural and operational optimization of cold storage system for enhanced energy efficiency, rapid cold release and economic benefits - Yuan Lv; Zhimei Zuo; Zizhuang Ma; Wang Cheng; Fan Wang; Chuanxiao Cheng; Zheng Ling; Lanlan Jiang; Tao Yu; Mingjun Yang; Lei Yang; Yu Liu; et al. (Journal of Cleaner Production, 2026)

The effects of soluble and insoluble salts on the small to large strain shear behaviour of reconstituted clayey loess - Luowen Li; Mengxue Huang; Ling Xu; Lu Zuo; Qian Huang; Shuai Cheng (Engineering Geology, 2026)

Effects of wastewater flow direction on sulfur-based autotrophic denitrification processes: operational patterns, denitrification performance and response mechanisms - Daheng Ren; Heng Dong; Wenke He; Zhiqiang Zuo; Xiangli Zeng; Xuchen Ba; Yang Yu; Haoran Xu; Guijiao Zhang; Ran Zeng; Jiamin Xu; Na Zhang; et al. (Chemical Engineering Journal, 2026)

Correction to: Landslide susceptibility mapping based on InSAR coherence rainfall components and deep learning: a case study of Lanping county in Southwest China - Yongfa Li; Zhuopei Ruan; Xiaoqing Zuo; Xiaona Gu; Yujuan Dong; Yongning Li; Chao Shi; Cheng Huang; Wenbin Xie; Qinheng Zou; Jingsong Xiao (Bulletin of Engineering Geology and the Environment, 2026)

Study on the cavitation characteristics and erosion mechanism of self-priming pulsed jets - Yanwei Liu; Yarui Li; Lejin Cheng; Weiqin Zuo; Haojie Jia; Chunlei Hua; Hongkai Han; Fengjie Zhang; Xiangyang Ma; Xianzhe Chen; Yu Zhang (Ocean Engineering, 2026)

Accelerated degradation of antiviral ribavirin by microalgae fuel cell (MFC), electricity generation and key metabolic process - Junhao Wang; Xinrui Qin; Jiajia Ge; Yongtao Cheng; Kang Li; Jun Liu; Kang Shan; Chuanyue Peng; Wenjing Yan; Juan Wang; Min Zuo; Ying Liu (Journal of Environmental Chemical Engineering, 2026)

Path to reducing pesticide input: Is agricultural production outsourcing effective? - Xingyi Zuo; Houjian Li; Cheng Wang; Andi Cao; Haoyu Wen (Ecological Economics, 2026)

Interpretable three-dimensional deep learning identifies and reveals the spatial Microstructure of multi-enzyme degradation of lignocellulose - Ziyi Tie; Xianduo Meng; Cheng Chen; Chuncheng Xu; Sasa Zuo (Bioresource Technology, 2026)

Landslide susceptibility mapping based on InSAR coherence rainfall components and deep learning: a case study of Lanping county in Southwest China - Yongfa Li; Zhuopei Ruan; Xiaoqing Zuo; Xiaona Gu; Yujuan Dong; Yongning Li; Chao Shi; Cheng Huang; Wenbin Xie; Qinheng Zou; Jingsong Xiao (Bulletin of Engineering Geology and the Environment, 2026)

A comprehensive study of turbid water consolidation and influence of outlet elevation on reservoir sediment management - Cheng-Chia Huang; Fong-Zuo Lee (Advances in Water Resources, 2026)

Spatio-temporal heterogeneity and multi-factor quantitative analysis of InSAR tropospheric delay in alpine-canyon regions - Jihong Zhang; Xiaoqing Zuo; Shipeng Guo; Cheng Huang; Xuefu Yue (International Journal of Remote Sensing, 2026)

Seven previously undescribed seco-abietane and seco-isopimarane type diterpenoids from Biscogniauxia sp. and their biological activities - Meng Zhang; Yang Yan; Wen-Song Bi; Liu-Yang Ma; Dan Hu; Liang-Dong Guo; Zuo-Cheng Qiu; Guo-Dong Chen; Huan Zhao; Hao Gao (Phytochemistry, 2026)

Elucidating the algicidal mechanisms and potential bioactive metabolites of Bacillus sp. WZU320 against Microcystis aeruginosa: A physiological and integrated multi-omics analysis - He Zhang; Zhongliang Zhang; Wenwen Zhang; Bangyue Zhang; Qizhen Xiang; Xinyue Ren; Hailong Zou; Yao Cheng; Jun Zuo; Zeshuang Wang; Zengling Ma; Peng Xiao; et al. (Algal Research, 2026)

A Large-Scale Micro-friction True Triaxial Apparatus for Analyzing the Failure Features of Coarse-Grained Soils Under Complex Stress Conditions - Jia-Jun Pan; Wei Zhao; Zhan-Lin Cheng; Yong-Zhen Zuo (Rock Mechanics and Rock Engineering, 2026)

Subseasonal Predictability of the North China Heat Extremes in Dynamical Models - Shanjun Cheng; Jinqing Zuo; Jianshuang Cao; He Huang; Liye He; Qiang Guo; Lijun Bian (Journal of Meteorological Research, 2026)

Identifying Neddylation-modified features to assess prognosis and immune efficacy in hepatocellular carcinoma - Zitao Liu; Cheng Zuo; Changlei Wu; Huakai Tian; Zhengming Zhu; Wenjie Zhu; Liang Sun (Apoptosis, 2026)

Resveratrol-Eu-layered double hydroxide nanocomposite alleviates radiation-induced lung injury through antioxidant and IL-17/NF-κB-associated anti-inflammatory effects - Fangxiao Cao; Junzhe Yang; Xiaoyi Cai; Xin Zuo; Yiming Wang; Li Du; Yuxin Lu; Xiaochen Cheng; Tingting Liu; Shan Ma; Feiyu Zhao; Shanyue Guan; et al. (Chemical Engineering Journal, 2026)

Perfusion process-oriented metabolic engineering enhances 1,3-dihydroxyacetone production efficiency in Gluconobacter thailandicus - Yang Sun; Zilong Hu; Yuwei Shan; Rui Wang; Tang Liu; Kuiqi Jin; Qingxuan Miao; Cheng Ye; Jianqi Nie; Daiyin Zuo; Yinbiao Xu; Hua Li; et al. (Chemical Engineering Journal, 2026)

Impact of meridional circulation on the record-breaking rainfall over South China in April 2024 - Chen Cang; Juneng Liew; Jianbo Cheng; Dongdong Zuo; Yuheng Zhao; Guolin Feng (Theoretical and Applied Climatology, 2026)

Performances and microbial mechanisms of trihalomethanes removal from tailwater in multi-stages constructed wetland - Yueyuan Wang; Shangwu Zuo; Jiawei Xie; Jianshi Huang; Xueqi Zhang; Fei Zhong; Shuiping Cheng (Journal of Environmental Chemical Engineering, 2026)

Microwave melting of lunar regolith simulant in an unchambered environment: Insights from physical model experiments - Jia-Qi Lu; Zheng-Wei Li; Xia-Ting Feng; Cheng-Dan He; Yong-Jun Wang; Yang Zuo; Jin Wang (International Journal of Rock Mechanics and Mining Sciences, 2026)

Pharmacological effects of cardamonin in metabolic diseases: a review on preclinical studies - Aizhi Zhang; AbdulRahman Muthanna; Yu Zhao Lee; Xuan Xin Yew; Rieyshmondraj Selvanathan; Zuo Shan Reuel Gan; Ji Wei Tan; Yu-Cheng Ho; Ming Tatt Lee; Chau Ling Tham (Inflammopharmacology, 2026)

Genome-Wide Identification and Expression Analysis of EBP Genes in Cotton - Lingyu Hao; Dongyun Zuo; Qiaolian Wang; Limin Lv; Youping Zhang; Yi Yang; Xue Zhang; Shuo Zhang; Guoli Song; Hailiang Cheng (Biochemical Genetics, 2026)

Exacerbated Impacts of Compound Dry‐Hot Events on Vegetation: Critical Thresholds and Spatial Vulnerability Dynamics in Northwest China - Shuyao Liu; Wenqing Zhang; Liu Liu; Depeng Zuo; Lei Cheng (International Journal of Climatology, 2026)
Global climate change has intensified the frequency and severity of compound dry‐hot events (CDHEs), posing more severe impacts on terrestrial ecosystems than individual extremes, particularly in Northwest China (NWC). However, a comprehensive probabilistic assessment of vegetation vulnerability under CDHEs, particularly, the identification of triggering thresholds for vegetation loss remains limited. This study employed standardised indices of vegetation (NDVI), drought (SPI) and hot conditions (STI) from 1982 to 2018 to develop a Vine copula framework for assessing vegetation vulnerability under CDHEs and identifying the corresponding triggering thresholds for vegetation loss. The results demonstrated that the standardised compound event indicator (SCEI) in NWC indicated a decreasing trend (−0.12 decade −1 ), reflecting the intensification of CDHEs. This intensification of CDHEs has led to greater ecosystem vulnerability in NWC. Under Severe Dry‐Severe Hot conditions (S4: SPI 1.3), the average probabilities of vegetation loss below the 50th, 30th, 20th and 10th percentiles were 51.2%, 42.3%, 36.2% and 27.2%, respectively. Different vegetation types (croplands, forests and grasslands) exhibited distinct vulnerability patterns, with grasslands being the most sensitive and forests the least. The average SPI/STI thresholds corresponding to vegetation loss below the 50th percentile (mild) and 10th percentile (extreme) were −0.71/0.72 and −1.08/1.35, respectively. It could provide a novel framework for assessing vegetation vulnerability under CDHEs, while simultaneously offering a profound comprehension of ecosystems' response mechanisms to CDHEs.

Divergent Mechanisms Drive Multi‐Decadal Drought Intensification in South America: A Trend Turning Analysis From 1958 to 2023 - Wei Lou; Cheng Sun; Bin Zuo; Menghao Dong; Zicen Song; Linfeng Shi; Yihua He; Yibing Tong (International Journal of Climatology, 2026)
South America is undergoing an unprecedented drought crisis, threatening water security, ecosystem integrity and socioeconomic stability. While individual extreme drought events are well documented, the temporal evolution and mechanistic drivers of long‐term drought intensification remain poorly understood. Here, we employ the Running Slope Difference (RSD)– t ‐test method to analyse Palmer Drought Severity Index (PDSI) and soil moisture data, revealing two critical regime shifts in Central South America (CSA) drought patterns since 1958. We identify an abrupt transition from wet to dry conditions circa 1978, followed by a pronounced acceleration in drought severity post‐2012. Random Forest attribution analysis demonstrates that these regime shifts stem from distinct driving mechanisms. The 1978 transition primarily reflects precipitation deficits linked to large‐scale atmospheric circulation changes, including enhanced subsidence and tropospheric warming that suppress convective activity. In contrast, the post‐2012 acceleration is predominantly driven by elevated vapour pressure deficit (VPD), triggered by land surface feedbacks. Specifically, progressive vegetation loss reduces evapotranspiration, creating a positive feedback loop where decreased atmospheric moisture enhances VPD, accelerates soil moisture depletion and amplifies vegetation stress. This identification of temporally distinct drought intensification mechanisms provides crucial insights for regional climate adaptation strategies. Our findings suggest that while the 1978 regime shift reflected primarily atmospheric forcing, recent drought acceleration is increasingly modulated by land‐atmosphere feedbacks—highlighting the critical role of vegetation conservation in future drought resilience.

Decoupling control of dissolved oxygen and water temperature using a state-space equation-based model predictive controller in recirculating aquaculture systems - Xinhui Zhou; Cheng Liu; Yinfeng Hao; Xianyu Zuo; Liming Zhou; Qingling Duan (Aquaculture International, 2026)

Reinforced π-conjugated organosulfur PDI polymer boosting peroxymonosulfate activation for photocatalytic degradation of bisphenol A - Pingping Lu; Qiuyi Ji; Xiaoqian Ye; Guanshun Wang; Yangbo Cheng; Wendi Zhou; Zhe Xu; Gancheng Zuo; Xin Jin; Guoyang Zhang; Limin Zhang; Huan He (Chemical Engineering Journal, 2026)

Association of Statin use with Parkinson’s Disease Progression in a Prospective Cohort Study and Multi-omics Analyses - Li Ke; Ziyi Chen; Fangzhou Fan; Xiaoya Zou; Li Yi; Hongzhou Zuo; Oumei Cheng (Journal of Molecular Neuroscience, 2026)

Light-AdaPSPNet: A novel lightweight adaptive weighted semantic segmentation network based on PSPNet for extracting Spartina alterniflora from dual-polarimetric SAR images - Zhenjin Li; Zhiyong Wang; Huiyang Zhang; Yanan Zuo; Xiaotong Liu; Baojing Zhang; Ze Chen; Silong Cheng (Computers and Electronics in Agriculture, 2026)

S-Scheme MOF heterostructures as peroxymonosulfate activators for enhanced photocatalytic degradation of sulfamethoxazole: Mechanisms and degradation pathways - Menghui Zhu; Meng Wang; Yujun Cheng; Jiasi Zuo; Ziyi Gao; Xiaotong Sun; Xiaoqing Chen; Qi Liu (Journal of Environmental Chemical Engineering, 2026)

An integrated biorefinery strategy for dual valorization of xylose residue unlocks high-yield glucose and fully lignin-based adhesives - Cheng Zuo; Xin-Yi Hui; Pin-An Xin; Hao-Nan Qi; Xiaojun Shen; Jia-Long Wen; Tong-Qi Yuan (Chemical Engineering Journal, 2026)

Distinct dynamical processes of dry and wet heatwaves in North China: observational and modeling perspectives - Shanjun Cheng; Jinqing Zuo; Yu Nie; Jiacan Yuan; He Huang; Liye He (Climate Dynamics, 2026)

Mechanism by Which Exogenous GABA Enhances the Tolerance of Potatoes to Low-Potassium Conditions - Fengjuan Wang; Ruijie Zuo; Shang Shi; Junrong Cheng; Yifei Lu; Bi Ren; Liming Lu; Liqin Li (American Journal of Potato Research, 2026)

Cerebral microbleeds aggravate severity of motor function, cognitive and emotional status in Parkinson’s disease - Tian Feng; Hongzhou Zuo; Xinyi Du; Juan Peng; Oumei Cheng (Acta Neurologica Belgica, 2026)

Predicting cyanobacteria removal efficiency in flocculation-DAF: Improving interpretable automated machine learning with CVAE data augmentation - Xiao Zhao; Zijun Yang; Jianjian Wei; Zixuan Wang; Cheng Cheng; Wanyi Li; Jihang Li; Yutong Zhang; You Zuo; Jun Hou (Water Research, 2026)

Ceritinib–ibuprofen synergistic hepatotoxicity: Insights from real-world data and liver organoid models - Shiyi Tan; Yun Yang; Li Ma; Xulei Zuo; Jianhua Rao; Yuepu Pu; Feng Cheng; Zhongze Gu; Juan Zhang (Toxicology, 2026)

A novel bathymetric mapping framework integrating indirect inversion of ICESat-2 and multi-source remote sensing data - Zijia Wang; Sheng Nie; Cheng Wang; Jian Zuo; Xiaohuan Xi; Xiaolin Bian; Xiaoxiao Zhu; Bisheng Yang (Remote Sensing of Environment, 2026)

Neuroprotective Effect of Umbelliferone Against Chemotherapy-Induced Neurotoxicity in Rats via Alteration of NF-κB, PPAR-δ, and Mitochondrial Apoptosis Pathways - Xiaohui Li; Yu Han; Han Tian; Zihui Cheng; Jingjing Zuo; Qingxia Shen (Molecular Neurobiology, 2026)

Does pluralistic collaborative governance between governmental and social actors promote urban carbon emission reduction? Evidence from 107 cities of China - Jingru Li; Qianchang Luo; Yanbin Cheng; Jian Zuo (Urban Climate, 2025)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Combined toxicity of microplastics and heavy metals to terrestrial plants: A global meta-analysis integrating machine learning predictions - Ye-Qian Zhen; Tian-Hao Che; Yu-Xuan Song; Ya-Ming Wan; Hai-Han Jiang; Zuo-Zhou Yu; Miao Yu; Shi-Qi Xu; Cheng-Yong Li; Jing-Ya Zhou (Journal of Environmental Chemical Engineering, 2025)

Arbuscular mycorrhizal fungi induced microbial community restructuring and plant transcriptional adaptation drive enhanced phytoremediation of heavy metal-antibiotic co-contaminated sediment - Xueqi Zhang; Xueqing Sui; Zhihao Luo; Jianshi Huang; Shangwu Zuo; Liuyang Li; Yuefang He; Shuiping Cheng (Chemical Engineering Journal, 2025)

Genome-wide identification and functional annotation of the ascorbate peroxidase (APX) gene family in cotton: putative roles in reactive oxygen species (ROS) homeostasis within pigment glands - Xue Zhang; Dongyun Zuo; Qiaolian Wang; Limin Lv; Youping Zhang; Yi Yang; Lingyu Hao; Shuo Zhang; Guoli Song; Hailiang Cheng (Planta, 2025)

Association of MSH2, MSH6, and MLH1 polymorphisms with susceptibility and survival in lung cancer patients - Jing Cheng; Chao Zuo; Dongli Yang; Yi Liu; Yu Wang; Yongchao Qiao (Genes & Genomics, 2025)

Study on high-content screening-based allelopathic inhibition by Macleaya cordata extracts on Microcystis aeruginosa and its mechanism - Linna Shao; Shi Huang; Liexiong Zhang; Yu Wu; Cai Cheng; Xiaoliang Guo; Jie Yu; Xingyu Xiang; Wenqi Zhang; Xuehan Xu; Lingzi Zuo; Lingling Feng (Algal Research, 2025)

Collapse of cetacean biodiversity in the North Yellow Sea: Social media and AIS data uncover anthropogenic threats and conservation hotspots - Zhaolong Cheng; Yongtao Li; Jun Wang; Mingxiang Niu; Tao Zuo (Ocean & Coastal Management, 2025)

Fe(Ⅱ/Ⅲ) cycling-based buffering strategy to mitigate sulfide and nitrate overflow in sulfur autotrophic denitrification process under wastewater quality fluctuations - Daheng Ren; Zhiqiang Zuo; Xuchen Ba; Wenke He; Shuaikang Yuan; Yongxian Cen; Guijiao Zhang; Jiamin Xu; Na Zhang; Yilu Sun; Aijie Wang; Hao-Yi Cheng (Water Research, 2025)

Multielement conodont apparatus (Cornudina) from the Lower Triassic of China, revealed by high-resolution X-ray microtomography - Wu-Jun Xu; Zuo-Yu Sun; Shuang Liu; Cheng Ji; Hao Lu; Zhao-Liang Ma; Fei-Yang Wu; Shou-Ming Chen; Jian-Dong Huang (Palaeoworld, 2025)

Geochemical characteristics and UPb chronology of detrital zircon in the Neogene Shizigou Formation, Qigequan area, western Qaidam Basin: Implications for tectonics, paleoclimate, and uranium sources - Chao Zhang; Shanbo Wang; Yinhang Cheng; Jiarun Tu; Reng’’an Yu; Ping Feng; Zhifeng Zuo; Yongliang Zang (Journal of Geochemical Exploration, 2025)

Chemical characterization and causes of differences in surface sediments of sand dunes in northern China under wind-water composite effects – A case study of the Kubuqi Desert - Cheng Xi; Hejun Zuo; Min Yan; Yu Yan (Geomorphology, 2025)

Plasmon-driven mechanistic insights into diphenylacetylene oxidation: A molecular-level investigation via in situ SERS - Yujun Cheng; Kecen Chen; Hongbo Yu; Ziyi Gao; Menghui Zhu; Jiasi Zuo; Qi Liu; Xiaoqing Chen (Chemical Engineering Journal, 2025)

Tough, stretchable, and adhesive ionogels for impact resistance and wearable ionotronics - Yan Cheng; Zhuoyou Gao; Jiali Zhang; Yushu Liu; Yajie Li; Fangzheng Zuo; Xianling Wang; Hongzan Song (Chemical Engineering Journal, 2025)

Damage Evolution Modeling of Karst-Affected Dolomite Under Uniaxial Compression - Cheng Li; Chen Wang; Yujun Zuo; Zichen Li; Chaoyuan Yong; Mingguang Wu (Geotechnical and Geological Engineering, 2025)

Deinococcus lichenicola sp. nov., A Bacterium Isolated from a Lichen Sample - Guo-Hua Chen; Lian-Shuang Xiong; Rui Yang; Shu-Ya Zuo; Qing Yuan; Li-Song Wang; Cheng-Lin Jiang; Xin-Yu Wang; Yi Jiang (Current Microbiology, 2025)

Challenges in Predicting Yangtze River Basin Summer Temperatures: The Role of Atmospheric Circulation and Tropical SST Forcing - Jinqing Zuo; Xiaolong Jia; Tao Feng; Shanjun Cheng; Hui Gao; Xuannan Wang; Li Li; Jingpeng Liu; Jie Tang; Lei Wang (International Journal of Climatology, 2025)
The densely populated and economically crucial Yangtze River Basin (YRB) in China has experienced an increasing trend of high‐temperature events during recent summers, highlighting the importance of skillful seasonal prediction for effective mitigation and adaptation. However, the sources of predictability and origins of prediction errors for YRB summer temperatures remain poorly understood. This study investigates the predictability of YRB summer (July–August) temperatures using hindcasts from three state‐of‐the‐art dynamical climate models to better understand these sources. While all models demonstrate some skill at a 0‐month lead, this capability becomes severely limited at lead times of 1 month or longer. Analysis of the models' ability to simulate the driving physical mechanisms reveals that while they reasonably capture the observed relationship between YRB summer temperatures and the associated local atmospheric circulation pattern linked to a Eurasian mid‐to‐high latitude wave train, significant uncertainties in predicting this wave train itself constrain overall skill. Furthermore, observational evidence shows a significant out‐of‐phase relationship between YRB summer temperatures and concurrent sea surface temperature (SST) anomalies in the equatorial central–eastern Pacific, a relationship that the models fail to reproduce. This failure stems from varying model biases in simulating the atmospheric circulation response to equatorial Pacific SST forcing, hindering their ability to capture the Pacific–YRB teleconnection. Therefore, deficiencies in simulating both the Eurasian circulation and the tropical Pacific forcing significantly contribute to the limited seasonal prediction skill for YRB summer temperatures, underscoring the need for improved representation of mid‐latitude dynamics, tropical air–sea interactions and associated atmospheric teleconnections in dynamical models.

Alternative splicing of OsNPR3 promoted by the bacterial TAL effectors-targeted splicing regulator OsRBP11 antagonizes OsNPR1 function and enhances disease susceptibility in rice - Xiaochen Chen; Xiaohui Yao; Fang Yan; Shaofang Li; Zuo-Dong Wang; Fu-You Yin; Miao Zhou; Zhen Wang; Lina Qin; Baoguo Zhao; Kai Lu; Liyuan Zhang; et al. (Molecular Plant, 2025)

Multifunctional regulation of trace tetra-carboxyl additive for stable Zn anodes in aqueous electrolytes - Xi Cheng; Min Sang; Danying Zuo; Jing Xu; Hongjun Li; Hongwei Zhang (Chemical Engineering Journal, 2025)

Amazon deforestation intensifies atmospheric aridity through locally dominant biophysical mechanisms - Mengqi Cheng; Qinglong You; Zhiyan Zuo; Mingcai Li; Deliang Chen; Niklas Boers (Agricultural and Forest Meteorology, 2025)

Profile of climate extremes vulnerability in China during 1991–2022 - Fangyuan Cheng; Meiyu Chang; Zhiyan Zuo; Wei Mei (Science Bulletin, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Treatment with inactivated Metschnikowia bicuspidata protects against the later infection in Chinese mitten crab Eriocheir sinensis - Tianqi Yu; Yali Li; Weilin Wang; Xingye Lian; Junlei Cheng; Jiajun Zuo; Lingling Wang; Linsheng Song (Fish & Shellfish Immunology, 2025)

Switchable adhesion of gecko-inspired adhesives on curved substrates by magnetically induced self-peeling - Changlin Shen; Yonggui Cheng; Zimo Zhao; Randong Zuo; Ming Liu; Bo Zhang; Yin Yao; Zhilong Peng; Shaohua Chen (Chemical Engineering Journal, 2025)

The functional role of P2 purinergic receptors in the progression of gastric cancer - Fei-long Zou; Ji-peng Liu; Cheng Zuo; Peng-fei He; Jin-xiong Ye; Wen-jun Zhang (Purinergic Signalling, 2025)

Mechanisms and modeling of nitrogen transport and removal in catchments with ditch-pond systems: a review - Cheng Sun; Ying Zhang; Nuo Liu; Qingqing Zuo; Lei Chen (Journal of Environmental Management, 2025)

Effects and interaction of humidex and air pollution on influenza: A national analysis of 319 cities in mainland China - Qi Gao; Baofa Jiang; Michael Tong; Hui Zuo; Chuanlong Cheng; Yuqi Zhang; Sihao Song; Liang Lu; Xiujun Li (Journal of Hazardous Materials, 2025)

Can saturation levels’ optimization abate the pressure of C/N ratio variation and low temperature on vertical flow constructed wetland for nitrogen removal? - Shangwu Zuo; Yueyuan Wang; Jiawei Xie; Juan Wu; Fei Zhong; Yebin Lu; Yang Yang; Shuiping Cheng (Journal of Environmental Chemical Engineering, 2025)

A testis-specific heat shock protein gene plays a critical role in male fertility in the fall armyworm - Yuchen Zhao; Pei Wang; Yalan Cheng; Siyu Tian; Junfeng Zuo; Qianguang Fang; Chenxue Ling; Subba Reddy Palli; Xien Chen (Insect Biochemistry and Molecular Biology, 2025)

Effect-directed analysis of the overlooked Ralstonia insidiosa induced Listeria monocytogenes aggregation under nutrient stress - Xifeng Zuo; Pin Chen; Zhe Liu; Qingyan Pan; Keying Li; Si Cheng; Ailing Guo (Food Bioscience, 2025)

Digital Guide and Handheld Robot-Assisted Tibial Tunnel Placement in Anterior Cruciate Ligament Reconstruction: A Cadaver Study - Hao-Cheng Zuo; Ping-Lang Yen.; Shuo-Suei Hung (Journal of Medical and Biological Engineering, 2025)

Extreme Drought Decreases the Stability of Above‐ but Not Below‐Ground Productivity Across Eurasian Steppes - Yingjie Yan; Chong Xu; Yann Hautier; Hongqiang Wang; Yuguang Ke; Honghui Wu; Jinsong Wang; Changjin Cheng; Xiaoan Zuo; Wentao Luo; Melinda D. Smith; Alan K. Knapp; et al. (Global Change Biology, 2025)
Ecological stability plays a crucial role in determining the sustainability of ecosystem functioning and nature's contribution to people. Although the disruptive effects of extreme drought on ecosystem structure and functions are widely recognized, their effect on the stability of above‐ and belowground productivity remains understudied. We assessed the effects of drought on ecosystem stability using a 3‐year drought experiment established in six Eurasian steppe grasslands. The treatments imposed included ambient precipitation, chronic drought (66% reduction in precipitation throughout the growing season), and intense drought (complete exclusion of precipitation for two months during the growing season). We found that drought, irrespective of how it was imposed, reduced the stability of aboveground net primary productivity (ANPP) but had little impact on belowground net primary productivity (BNPP) stability. Reduced ANPP stability under drought was primarily attributed to changes in subordinate species stability, with mean annual precipitation (MAP) and its variability, historical drought frequency, and the aridity index (AI) also influencing responses to extreme drought. In contrast, BNPP stability was not related to any community factor investigated, but it was influenced by MAP variability and AI. Our findings that above‐ and belowground productivity stability in grasslands are differentially sensitive to multi‐year extreme drought under both common (MAP and AI) as well as unique drivers (plant community changes) highlight the complexity of predicting carbon cycle dynamics as hydrological extremes become more severe.

The heterogeneity of travel mode choice behavior under unplanned metro service disruptions - Qing-Chang Lu; Xin-Yu Zuo; Chao Chen; Zhi Dong; Peng-Cheng Xu; Jing Li (Transportation Research Part D: Transport and Environment, 2025)

Angle-resolved magneto-chiral anisotropy in a non-centrosymmetric atomic layer superlattice - Long Cheng; Mingrui Bao; Xue Zhang; Jingxian Zhang; Qun Yang; Qiang Li; Hui Cao; Dawei Qiu; Hui Li; Guanglei Cheng; Hua Zhou; Jian-Min Zuo; et al. (Science Bulletin, 2025)

Imaging brain white matter function using resting-state functional MRI - Gong-Jun Ji; Zaixu Cui; Ryan C.N. D’Arcy; Wei Liao; Bharat B. Biswal; Qing Zhang; Cheng Luo; Yu-Feng Zang; Zhaohua Ding; Xi-Nian Zuo; John C. Gore; Kai Wang (Science Bulletin, 2025)

Conodonts suggest a late Spathian (late Early Triassic) age for Thaisaurus chonglakmanii (Reptilia: Ichthyosauromorpha) from Thailand - Si-Yao Ye; Kui Wu; Zuo-Yu Sun; P. Martin Sander; Adun Samathi; Yuan-Yuan Sun; Cheng Ji; Varavudh Suteethorn; Jun Liu (Palaeoworld, 2025)

Identifying priority habitat for future spatial conservation and management decisions of East Asian finless porpoise within Miaodao Archipelago waters, China - Yongtao Li; Zhongxun Wu; Yongzhong Chu; Zhaolong Cheng; Tao Zuo; Mingxiang Niu; Jun Wang (Marine Environmental Research, 2025)

Corrigendum to “High leucine bioavailability improves beef quality by altering serum metabolism in beef cattle” [Meat Science volume 220 (2025) 109693] - Jishan An; Xiangchao Zhao; Yang Song; Huitian He; Zuo Wang; Xinyi Lan; Yu Ge; Lei Liu; Anwei Cheng; Weijun Shen; Fachun Wan (Meat Science, 2025)

Integration of SWAT-DPS and optimization algorithm for spatial design of ditch-pond systems in small agricultural catchments - Cheng Sun; Shibo Chen; Qingqing Zuo; Lei Chen; Zhenyao Shen (Journal of Hydrology, 2025)

Humanin alone and in combination with GnRHa therapy attenuates ovarian dysfunction induced by prepubertal cyclophosphamide chemotherapy in female mice - Liu Liu; Huawei Wang; Wen Wen; Shunqing Wang; Liqin Zuo; Yulin Cheng; Meng Rao; Yuru Ma; Li Tang (Reproductive Toxicology, 2025)

Spatial distributions, potential sources, and ecological risks of heavy metals in stream sediments in Zambia - Hongwei Sun; Junping Ren; Jie Wang; Jianzhong Yu; Libo Zuo; Xingyuan Wu; Chipilauka Mukofu; Alphet Phaskani Dokowe; Shuping Cao; Xujiang Cheng (Journal of Geochemical Exploration, 2025)

Spatiotemporal distribution of ichthyoplankton and their relationship with environmental factors in the waters around the Yellow River estuary, China - Mingxiang Niu; Feng Lu; Tao Zuo; Jun Wang; Yongtao Li; Zhaolong Cheng; Jianqiang Sun (Frontiers in Marine Science, 2025)
Introduction The Yellow River estuary serves as a crucial convergence point between the Yellow River and the Bohai Sea and is a vital spawning, nursery, and feeding ground for a variety of fish species. Ichthyoplankton are essential for the replenishment and sustainable use of fishery resources. To gain insights into the distribution of fish in these early life stages and examine in depth the impacts of environmental factors on their presence and abundance in the waters around the Yellow River estuary, in this study, we analyzed the temporal and spatial distribution of ichthyoplankton and their correlation with environmental variables. Methods Data were gathered from horizontal-trawl surveys conducted between April and July of 2020, 2021, and 2023. In instances where no eggs or larvae were caught, a two-stage Generalized Additive Model (GAM) was employed to evaluate the influence of environmental factors on the presence/absence (P/A model) and abundance, given presence (Density model). Results The results revealed that there were significant fluctuations in species richness both monthly and annually. Moreover, notable spatial disparities were identified in the distribution of abundance encompassing estuarine, settled, and migratory fish populations. The final model accounted for 38.69% and 39.80% of the deviance in the presence and abundance of ichthyoplankton, respectively. The two-stage GAM results highlighted that sea surface temperature (SST), chlorophyll a concentration, sea bottom salinity, and water depth were the dominant factors influencing the presence of ichthyoplankton. Moreover, a model incorporating SST, sea surface salinity, and distance to shore best described the abundance of ichthyoplankton when present. Discussion Our findings contribute to understand the spatiotemporal dynamics of ichthyoplankton and their influencing factors in the waters around the Yellow River estuary, which have important implications for fisheries management.

Sequential decline in cyanobacterial, total prokaryotic, and eukaryotic responses to backward flow in a river connected to Lake Taihu - Jun Zuo; Siyu Yang; Hans-Peter Grossart; Peng Xiao; He Zhang; Rui Sun; Guoyou Li; Haoran Jiang; Qihang Zhao; Meng Jiao; Yao Cheng; Zeshuang Wang; et al. (Water Research, 2025)

High leucine bioavailability improves beef quality by altering serum metabolism in beef cattle - Jishan An; Xiangchao Zhao; Yang Song; Huitian He; Zuo Wang; Xinyi Lan; Yu Ge; Lei Liu; Anwei Cheng; Weijun Shen; Fachun Wan (Meat Science, 2025)

Machine learning driven benchtop Vis/NIR spectroscopy for online detection of hybrid citrus quality - Tao Jiang; Weidan Zuo; Jianjun Ding; Shaofeng Yuan; He Qian; Yuliang Cheng; Yahui Guo; Hang Yu; Weirong Yao (Food Research International, 2025)

The haemocyte highly-expressed E-type prostanoid receptor regulates TNF expression during immune response of oyster Crassostrea gigas - Xuemei Cheng; Weilin Wang; Miren Dong; Junlei Cheng; Jiajun Zuo; Xiaoxu Zhou; Lingling Wang; Linsheng Song (Fish & Shellfish Immunology, 2025)

Dual targeting of FR+CD44 overexpressing tumors by self-assembled nanoparticles quantitatively conjugating folic acid-hyaluronic acid to the GSH-sensitively modified podophyllotoxin - Chaozheng Zhang; Yao Chen; Yi Zuo; Maolin Wang; Hongyu Chen; Chuanqi Wang; Yuening Cao; Yingjie Zeng; Ying Chen; Tingting Zhang; Xian Ge; Xiujun Cao; et al. (Chemical Engineering Journal, 2025)

Construction of a Cas9-targeted mutagenesis mini-library in the upland cotton genetic standard line (TM-1) - Yunfei Hao; Jiajia Feng; Yuanyuan Li; Zhangcheng Yuan; Pengfei Miao; Hailiang Cheng; Qiaolian Wang; Youping Zhang; Limin Lv; Dongyun Zuo; Ji Liu; Guoli Song (Plant Cell Reports, 2025)

Leifsonia stereocauli sp. nov., Isolated from Stereocaulon tomentosum Fr. Lichen - Shu-Ya Zuo; Lian-Shuang Xiong; Qing Yuan; Guo-Hua Chen; Rui Yang; Li-Song Wang; Cheng-Lin Jiang; Xin-Yu Wang; Yi Jiang (Current Microbiology, 2025)

Precipitation-induced biomass enhancement and differential allocation in Inner Mongolia's herbaceous and shrub communities - Xiangyun Li; Ya Hu; Zhaobin Song; Ping Cong; Huan Cheng; Xuebo Zheng; Wenjing Song; Ping Yue; Shaokun Wang; Xiaoan Zuo (Science of The Total Environment, 2024)

Evolutionary characteristics and structural dependence determinants of global lithium trade network: An industry chain perspective - Yonglin Li; Zhili Zuo; Jinhua Cheng; Deyi Xu (Resources Policy, 2024)

Response of the abundance and size of Acartia (Acartiura) hongi (Copepoda: Calanoida) copepodites to environmental variables in Laizhou Bay, Bohai Sea - Tao Zuo; Jun Wang; Jianqiang Sun; Yongtao Li; Mingxiang Niu; Zhaolong Cheng (Regional Studies in Marine Science, 2024)

Corrigendum to: “The protective effect of rutin against the cisplatin-induced cochlear damage in vitro” [Neurotoxicology vol. 90 (2022) 102–111] - Shimei Zheng; Chang Liu; Dongmei Tang; Zhiwei Zheng; Renchun Yan; Cheng Wu; Na Zuo; Jun Ma; Yingzi He; Shaofeng Liu (NeuroToxicology, 2024)

Rapid bromate determination using short-column ion chromatography-mass spectrometry: Application to bromate quantification during ozonation - Shi Cheng; Haolin Liu; Yanting Zuo; Feng Zhu; Huaicheng Zhang; Hao Zhang; Shouqiang Huang; Wentao Li; Zongli Huo; Aimin Li (Journal of Environmental Chemical Engineering, 2024)

Detrital clay mineral input reconstructed based on weathering records and its influence on organic matter enrichment: A case study of the Paleogene Shahejie Formation in the Dongpu Sag, Bohai Bay Basin - Rusi Zuo; Jingong Cai; Xiang Zeng; Shi Cheng (Journal of Asian Earth Sciences, 2024)

Concurrent trend turnings of drought severity across Afro-Eurasian continent since 1950 - Wei Lou; Cheng Sun; Bin Zuo (Global and Planetary Change, 2024)

Multi-stimuli geminate encryption based on triphenylethylene for advanced anti-counterfeiting - Zhuo-Cheng Li; Zuo-Qin Liang; Zi-Hang Zhang; Su-Hang Xu; Pu Wang; Guo-Liang Dai; Chang-Qing Ye; Xiao-Mei Wang (Chemical Engineering Journal, 2024)

Bioengineering human heavy-chain nanoferritin for glioblastoma multiforme-specific delivery and efficient immunotherapy - Han Yan; Wenting Cheng; Siyuan Qin; Jing Zuo; Lei Li; Jing Zhang; Qinxia Chang; Yonghao Yan; Shiqi Wang; Canhua Huang; Haiyuan Zhang (Chemical Engineering Journal, 2024)

Enhanced nitrogen removal from secondary effluent of municipal wastewater using denitrification filter: Feasibility of refractory organics as a carbon source - Qingfeng Cheng; Hui Tian; Wen-Bo Nie; Jun Li; Yanting Zuo; Lichao Nengzi; Erdeng Du; Mingguo Peng (Bioresource Technology, 2024)

Optimizing ABA-based chemically induced proximity for enhanced intracellular transcriptional activation and modification response to ABA - Zeng Zhou; Yue-Qi Wang; Xu-Nan Zheng; Xiao-Hong Zhang; Lu-Yao Ji; Jun-You Han; Ze-Cheng Zuo; Wei-Liang Mo; Li Zhang (Science China Life Sciences, 2024)

Blocking endogenous phosphorus release in sediments by a hydrotalcite mixture synthesized with natural sepiolite and discarded cans - Fulong Cheng; Jie Pan; Changxin Zhao; Wei Li; Yuting Peng; Zuo Zhang; Yanjuan Lin; Guowen Chen (Applied Clay Science, 2024)

The different impacts of functional network centrality and connectivity on the complexity of brain signals in healthy control and first-episode drug-naïve patients with major depressive disorder - Shanling Ji; Wei An; Jing Zhang; Cong Zhou; Chao-Gan Yan; Xiao Chen; Li-Ping Cao; Wei Chen; Yu-Qi Cheng; Yi-Ru Fang; Qi-Yong Gong; Wen-Bin Guo; et al. (Brain Imaging and Behavior, 2024)

Corrigendum to “Defense against Paramecium predation via long filament morphology favors the survival of Raphidiopsis raciborskii populations” [Harmful Algae 137 (2024) 102678] - Zeshuang Wang; Xiaoli Huang; Yangyang Wu; Xiang Hu; Qihang Zhao; Jun Zuo; Peng Xiao; Yao Cheng; He Zhang; Renhui Li (Harmful Algae, 2024)

Effect of elemental composition and phase transformation on lithium leaching behavior of micas in calcination-acid leaching process - Kesheng Zuo; Xuanping Zhou; Hao Wang; Zhihang Li; Kun Xiong; Hongfei Cheng (Applied Clay Science, 2024)

Diagnosis of systemic lupus erythematosus using cross-modal specific transfer fusion technology based on infrared spectra and metabolomics - Cheng Chen; Mingtao Wu; Enguang Zuo; Xue Wu; Lijun Wu; Hao Liu; Xuguang Zhou; Yang Du; Xiaoyi Lv; Chen Chen (Analytica Chimica Acta, 2024)

Characteristics of inhibition of Aspergillus flavus growth and degradation of aflatoxin B1 by cell-free fermentation supernatant of Bacillus velezensis 906 - Keying Li; Si Cheng; Zhe Liu; Qingyan Pan; Xifeng Zuo; Ailing Guo; Jun Lv (Food Bioscience, 2024)

Preparation and characterization of probiotic Bacillus velezensis 906 metabolites /potassium sorbate/ polyvinyl alcohol antimicrobial blend film - Si Cheng; Chao Yin; Keying Li; Zhe Liu; Qingyan Pan; Xifeng Zuo; Ailing Guo; Huawei Ma (Food Bioscience, 2024)

Experimental investigation on double-lap shear behavior of 3D printed austenitic stainless steel bolted connections - Wenkang Zuo; Man-Tai Chen; Si-Wei Liu; Xiang Yun; Ou Zhao; Yuner Huang; Bin Cheng (Engineering Structures, 2024)

Image compression–based DS-InSAR method for landslide identification and monitoring of alpine canyon region: a case study of Ahai Reservoir area in Jinsha River Basin - Xiaona Gu; Yongfa Li; Xiaoqing Zuo; Jinwei Bu; Fang Yang; Xu Yang; Yongning Li; Jianming Zhang; Cheng Huang; Chao Shi; Mingze Xing (Landslides, 2024)

A study of the stabilization and solidification of heavy metals in co-vitrification of medical waste incineration ash and coal fly ash - Huikang Song; Yaji Huang; Junfeng Pang; Zhiyuan Li; Zhicheng Zhu; Haoqiang Cheng; Jiawei Gao; Wu Zuo; Haiyun Zhou (Waste Management, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Natural harmaline acts as novel fluorescent probe for hypochlorous acid and promising therapeutic candidate for rheumatoid arthritis - Dongbin Zheng; Yi Zuo; Longxuan Li; Arlene McDowell; Yuening Cao; Xiaoping Ye; Houcheng Zhou; Cheng Peng; Yun Deng; Jun Lu; Yuyu Fang (Journal of Photochemistry and Photobiology B: Biology, 2024)

Interception of internal phosphorus release from sediments by lanthanum-modified shrimp shell biochar in two application modes - Fulong Cheng; Zuo Zhang; Changxin Zhao; Yuting Peng; Maoyu Liao; Jianxin Fan (Journal of Cleaner Production, 2024)

Unveiling the secrets of bioelectrochemical system coupled with constructed wetland (BES-CW): A comprehensive review on refractory organics removal - Jiawei Xie; Shangwu Zuo; Fei Zhong; Shuiping Cheng (Journal of Cleaner Production, 2024)

Na+ orientates Jahn-Teller effect to tune Li+ diffusion pathway and kinetics for Single-Crystal Ni-rich LiNixCoyMn1-x-yO2 cathode materials - Jiyuan Jian; Xing Xu; Xiaoyi Pan; Guokang Han; Rang Xiao; Ziwei Liu; Dandan Sun; Xin Zhang; Qingjie Zhou; He Zhu; Geping Yin; Hua Huo; et al. (Chemical Engineering Journal, 2024)

Explainable artificial intelligence models for mineral prospectivity mapping - Renguang Zuo; Qiuming Cheng; Ying Xu; Fanfan Yang; Yihui Xiong; Ziye Wang; Oliver P. Kreuzer (Science China Earth Sciences, 2024)

Photobiomodulation Increases M2-Type Polarization of Macrophages by Inhibiting Versican Production After Spinal Cord Injury - Zhi-Hao Zhang; Ting-Yu Wu; Cheng Ju; Xiao-Shuang Zuo; Xuan-Kang Wang; Yang-Guang Ma; Liang Luo; Zhi-Jie Zhu; Zhi-Wen Song; Zhou Yao; Jie Zhou; Zhe Wang; et al. (Molecular Neurobiology, 2024)

Distribution of modified Circumpolar Deep Water and its threat in Vincennes Bay, East Antarctica - Wenjun Ye; Lingqiao Cheng; Yujiro Kitade; Song Hu; Juncheng Zuo (Journal of Oceanology and Limnology, 2024)

A partial siphon operational strategy strengthens nitrogen removal performance in partially saturated vertical flow constructed wetlands - Shangwu Zuo; Yueyuan Wang; Juan Wu; Fei Zhong; Lingwei Kong; Yue Chen; Shuiping Cheng (Chemosphere, 2024)

GhHDZ76, a cotton HD-Zip transcription factor, involved in regulating the initiation and early elongation of cotton fiber development in G. hirsutum - Cuicui Wu; Shuiping Xiao; Xianliang Zhang; Wenbin Ren; Xiaoxia Shangguan; Shuyan Li; Dongyun Zuo; Hailiang Cheng; Youping Zhang; qiaolian Wang; Limin Lv; Pengbo Li; et al. (Plant Science, 2024)

A new strategy for utilization of gasification ash: Manganese oxides-modified activated carbon for efficient copper citrate removal - Mingyang Sun; Jiahui Miao; Xie Tong; Mei Zuo; Zhicheng Song; Hong Chen; Guanghuan Cheng (Journal of Environmental Management, 2024)

Defense against Paramecium predation via long filament morphology favors the survival of Raphidiopsis raciborskii populations - Zeshuang Wang; Xiaoli Huang; Yangyang Wu; Xiang Hu; Qihang Zhao; Jun Zuo; Peng Xiao; Yao Cheng; He Zhang; Renhui Li (Harmful Algae, 2024)

Soil wind erosion, nutrients, and crop yield response to conservation tillage in North China: A field study in a semi-arid and wind erosion region after 9 years - Fahui Jiang; Xinwei Xue; Liyan Zhang; Yanyan Zuo; Hao Zhang; Wei Zheng; Limei Bian; Lingling Hu; Chunlei Hao; Jianghong Du; Yanhua Ci; Ruibao Cheng; et al. (Field Crops Research, 2024)

Facilitating the fabrication of diverse bio-based nanomaterials from bamboo using one-pot hydrated deep eutectic solvent pretreatment - Xin-Yi Hui; Cheng Zuo; Ying Xu; Bo Wang; Jia-Long Wen; Tong-Qi Yuan (Chemical Engineering Journal, 2024)

Rapid, sensitive, and visual detection of pseudorabies virus with an RPA-CRISPR/EsCas13d-based dual-readout portable platform - Dong You; Tong Xu; Bing-Zhou Huang; Fang Wu; Li-Shuang Deng; Zhe-Yan Liu; Liang-Peng Ge; Zuo-Hua Liu; Jing Sun; Xiu Zeng; Yuan-Cheng Zhou; Si-Yuan Lai; et al. (Analytica Chimica Acta, 2024)

Influence of temperature on performance and mechanism of advanced synergistic nitrogen removal in lab-scale denitrifying filter with biogenic manganese oxides - Qingfeng Cheng; Hui Tian; Yanting Zuo; Lichao Nengzi; Erdeng Du; Mingguo Peng; Xiuwen Cheng (Chemosphere, 2024)

Response of extreme precipitation to urban expansion over the Guangdong-Hong Kong-Macao Greater Bay Area - Fang Yang; Bo Pang; Lixiang Song; Hongguang Cheng; Sicong Zhou; Ziqi Zheng; Dingzhi Peng; Depeng Zuo (Urban Climate, 2024)

Does invasive submerged macrophyte diversity affect dissimilatory nitrate reduction processes in sediments with varying microplastics? - Xueyuan Gao; Xiaowei Li; Yingcai Wang; Cheng Lin; Yanxia Zuo; Xiaolu Li; Wei Xing (Journal of Hazardous Materials, 2024)

Development of a novel polydopamine-imprinted MOFs targeted for removal of refractory organic pollutants: Synergistic mechanisms of adsorption and degradation - Jianxin Yi; Jinquan Wan; Yan Wang; Yongwen Ma; Zhicheng Yan; Shiyu Zuo; Cheng Zeng; Wenhui Yuan (Journal of Cleaner Production, 2024)

A model coupling ecological and hydrodynamic processes for simulating the biogeomorphology of a coastal salt marsh - Ke-Hua Zhu; Jian Zeng; Zhen-Ming Ge; Yin Zuo; Shi-Hua Li; Lei-Hua Zhao; Yu Han; Hai-Feng Cheng; Pei Xin (Ecological Modelling, 2024)

Confinement effect of FeMOFs glass enhances the proton coupled electron transfer reaction for the organic pollutants polymerization toward sustainable water purification - Shiyu Zuo; Yichen Ding; Haoshan Cheng; Zeyu Guan; Xiaohu Li; Dongya Li (Chemical Engineering Journal, 2024)

A competitive strategy toward 1 T/2H MoS2 to balance impedance for optimizing electromagnetic wave absorption - Qilin Jiang; Lei Xu; Zhimeng Tang; Cheng Xie; Junyu Lu; Zhaohui Han; Di Zhang; Changhao Zuo (Chemical Engineering Journal, 2024)

Occurrence of the calanoid copepod Acartia (Odontacartia) ohtsukai in Laizhou Bay, the Bohai Sea, China, and its relationship with environmental factors - Tao Zuo; Di Wang; Yongtao Li; Mingxiang Niu; Zhaolong Cheng; Jun Wang (Frontiers in Marine Science, 2024)
In this study, we examined the short-term variation in the abundance of copepod Acartia specimens, identified previously as Acartia pacifica , in Laizhou Bay, an estuarine bay in the southern Bohai Sea in northern China. Monthly samples were collected from May 2011 to April 2012, excluding December 2011 and January to February 2012 due to ice. Based on its morphological characteristics, Acartia ohtsukai was distinguishable from A. pacifica for the first time in Laizhou Bay. A. ohtsukai was sporadically present from summer to autumn, with the highest abundance and occurrence in September. It appeared in June when the water temperature was above 20°C, and disappeared in November when the water temperature decreased to less than 10°C. During the surveyed months, A. ohtsukai was more commonly found inshore with salinity less than 28 than offshore in the bay. Correlation analysis revealed that temperature and chlorophyll a concentration significantly influenced the monthly variations in A. ohtsukai abundance. We also compared the occurrence of A. ohtsukai with that of three species from the genus Tortanus ( Tortanus derjugini , Tortanus forcipatus , and Tortanus spinicaudatus ) in Laizhou Bay. The coexistence of A. ohtsukai and T. derjugini in the bay suggests that their ecological habitats are similar to those of brackish-water species.

Cyanidin-3-O-glucoside protects Zearalenone-induced in vitro maturation disorders of porcine oocytes by alleviating NOX4-dependent oxidative stress and endoplasmic reticulum stress in cumulus cells - Xiuxiu Li; Yu Tian; Ning Zuo; Jiatian Tang; Shunfeng Cheng; Lan Li; Jinghe Tan; Jianxin Zhang; Wei Shen (Chemosphere, 2024)

Spatio-temporal detection of agricultural disaster vulnerability in the world and implications for developing climate-resilient agriculture - Wenjing Cheng; Yuheng Li; Wenjie Zuo; Guoming Du; Monika Stanny (Science of The Total Environment, 2024)

Geomorphological and geological characteristics reflecting the Holocene activity of the Dalangsonggou fault, eastern Tibetan Plateau - Mingjian Liang; Feipeng Huang; Hong Zuo; Cheng Liao; Weiwei Wu; Kai Sun; Yue Gong (Quaternary International, 2024)

Robust and efficient Iron-Based electrodes for hydrogen production from seawater at high current density above 1000 mA cm−2 - Xian Zhang; Huanyu Zhu; Ziteng Zuo; Mengtian Jin; Ouwen Peng; Qing Lian; Yulan Huang; Peng Cheng; Zhong Ai; Shengling Xiang; Abbas Amini; Shaoxian Song; et al. (Chemical Engineering Journal, 2024)

Reference Intervals of Serum Iodine Concentration in Chinese Pregnant Women - Yi Wu; Huan-huan Long; Su-juan Zhang; Min-Min Li; Chao-gang Chen; Cheng Wang; Zheng-yu Sheng; Yan-bin Ye; Shu-yu Zuo; Wen-jing Pan; Zhao-min Liu (Biological Trace Element Research, 2024)

Branched-chain amino acids in ruminant nutrition: Function effects and summary of recent advances - Jishan An; Huitian He; Xinyi Lan; Lei Liu; Zuo Wang; Yu Ge; Weijun Shen; Anwei Cheng; Fachun Wan (Animal Feed Science and Technology, 2024)

Fabrication of Carbon Dots with Singlet Oxygen Generation and Their Potential Photodynamic Therapy Applications - Pengli Zuo; Jun Peng; Yuyang Yao; Wei Tan; Lan Cheng; Jinyu Zhang; Xiuhua Lu (Journal of Fluorescence, 2024)

Live chicken body fat measurement technology based on bio-electrical impedance - Jiaming Zuo; Jinping Liang; Shangshang Cheng; Yuelin Deng; Zhenhui Li; Qinghua Nie; Dexiang Zhang; Xiquan Zhang; Zhen Li; Hongmei Li (Computers and Electronics in Agriculture, 2024)

Petrochemical wastewater treatment in a full-scale biological aerated filter system: Insight into the mechanism of performance deterioration - Hui Wang; Beibei Dai; Feng Gao; Xiaolei Cao; Xuan Ji; Lushen Zuo; Chang Cheng; Ling Jiang (Chemical Engineering Journal, 2024)

Advances in biotin biosynthesis and biotechnological production in microorganisms - Jia-Run Zhao; Si-Qi Zuo; Feng Xiao; Feng-Zhu Guo; Lu-Yi Chen; Ke Bi; Dong-Yuan Cheng; Zhi-Nan Xu (World Journal of Microbiology and Biotechnology, 2024)

Gastrodin Regulates PI3K/AKT-Sirt3 Signaling Pathway and Proinflammatory Mediators in Activated Microglia - Han-Jun Zuo; Peng-Xiang Wang; Xue-Qi Ren; Hao-Long Shi; Jin-Sha Shi; Tao Guo; Cheng Wan; Juan-Juan Li (Molecular Neurobiology, 2024)

Unusually weak signal of summer surface air temperature change over North China - Fangyuan Cheng; Zhiyan Zuo; Kaiwen Zhang; Meiyu Chang; Dong Xiao (International Journal of Climatology, 2024)
Under global warming, the summer surface air temperature (SAT) change signal in the northern mid‐latitudes is generally the most significant, while the SAT change in North China (NC) shows distinct local characteristics. Using simulations from the Coupled Model Intercomparison Project Phase 6 and observation from Berkeley Earth Surface Temperature, this study reveals an unusually weak signal of summer SAT change in NC since the 1960s. This uniquely weak signal can be attributed to the small net contribution of external forcings, mainly from anthropogenic greenhouse gases (GHG) and aerosols (AA). Compared to other land regions in the same latitudinal band, the GHG‐induced warming was weaker and AA‐induced cooling was stronger in NC, resulting in the weakest SAT change signal and thus the lowest signal‐to‐noise ratio. This weaker GHG‐induced warming plays a more important role in the SAT change difference between NC and other land regions in the same latitudinal zone. Under different emission scenarios in the future, the signal‐to‐noise ratio in NC will become as large as those in the other land regions in the same latitudinal band and the northern hemisphere, which is partly due to the smaller relative differences in the SAT change signal between NC and the other two regions. The projections of SAT change indicate that climate change in NC will probably become more violent and vulnerable.

Attempts to obtain clean biochar from hyperaccumulator through pyrolysis: Removal of heavy metals and transformation of phosphorus - Zhiyuan Li; Yaji Huang; Zhicheng Zhu; Mengzhu Yu; Haoqiang Cheng; Hao Shi; Yixuan Xiao; Huikang Song; Wu Zuo; Haiyun Zhou; Sheng Wang (Journal of Hazardous Materials, 2024)

Current-use pesticides monitoring and ecological risk assessment in vegetable soils at the provincial scale - Wei Zuo; Yang Zhao; Peipei Qi; Chunrong Zhang; Xueping Zhao; Shenggan Wu; Xuehua An; Xinju Liu; Xi Cheng; Yijun Yu; Tao Tang (Environmental Research, 2024)

Cascade fractionation of bamboo shoot shells into high-yield xylose, easily digestible cellulose and high-quality lignin nanoparticles by tailored catalytic hydrothermal–hydrated alkaline deep eutectic solvents pretreatment - Cheng Zuo; Ying Xu; Xin-Yi Hui; Ling-Hua Xu; Jia-Long Wen; Tong-Qi Yuan (Chemical Engineering Journal, 2024)

Pelagibacterium flavum sp. nov., Isolated from Soil Sample - Xue-Mei Chen; Zu-Zhen Yang; Si-Rong He; Lian-Shuang Xiong; Qing Yuan; Shu-Ya Zuo; Cheng-Lin Jiang; Yi Jiang (Current Microbiology, 2024)

An explainable unsupervised risk early warning framework based on the empirical cumulative distribution function: Application to dairy safety - Junyi Yan; Lei Sun; Enguang Zuo; Jie Zhong; Tianle Li; Chen Chen; Cheng Chen; Xiaoyi Lv (Food Research International, 2024)

Bright photoactivatable probes based on triphenylethylene for Cu2+ detection in tap water and tea samples - Zuo-Qin Liang; Dong-Dong Song; Zhuo-Cheng Li; Su-Hang Xu; Guo-Liang Dai; Chang-Qing Ye; Xiao-Mei Wang; Xu-Tang Tao (Food Chemistry, 2024)

Parametric topology optimization design and analysis of additively manufactured joints in spatial grid structures - Man-Tai Chen; Wenkang Zuo; Yangyu Chen; Ou Zhao; Bin Cheng; Jincheng Zhao (Engineering Structures, 2024)

Crucial role of the surface hydroxyl groups induced by oxygen vacancies on α-Fe0.9Zn0.1OOH during interfacial peroxymonosulfate activation for meclofenamic acid degradation - Tianhao She; Jimin Shen; Zhehao Wang; Pengwei Yan; Xueyan Li; Shuyu Wang; Jinxiang Zuo; Yizhen Cheng; Jing Kang; Binyuan Wang; Shengxin Zhao; Zhonglin Chen (Chemical Engineering Journal, 2024)

Synergistic mechanism of surface oxygen vacancies and metal sites on Al-substituted NiFe2O4 during peroxymonosulfate activation in the solid-water interface for 2,4-D degradation - Jinxiang Zuo; Donglei Fu; Pengwei Yan; Shuyu Wang; Yabin Li; Linlu Shen; Yizhen Cheng; Jimin Shen; Jing Kang; Zhonglin Chen (Chemical Engineering Journal, 2024)

Unveiling the microstructure, materials, and painting period of ancient wall paintings at Shanxi Xianqing Temple, China - Weihan Zou; Sok Yee Yeo; Peng Cheng; Xiaodi Zuo; Peng Zhao; Shijie Li (Archaeological and Anthropological Sciences, 2024)

Unraveling the single-atom Fe–N4 catalytic site selectivity generate singlet oxygen via activation of persulfate: Polarizing electric fields changes the electron transfer pathway - Yan Wang; Shiyu Zuo; Cheng Zeng; Jinquan Wan; Zhicheng Yan; Jianxin Yi (Chemosphere, 2023)

Hydrogen production and CO2 capture from Linz-Donawitz converter gas via a chemical looping concept - Huicong Zuo; Chunqiang Lu; Lei Jiang; Xianming Cheng; Zhiqiang Li; Yuelun Li; Danyang Li; Hua Wang; Kongzhai Li (Chemical Engineering Journal, 2023)

NLRP3/miR-223-3p axis attenuates neuroinflammation induced by chronic intermittent hypoxia - Cheng Wu; Wen Xing; Yuanxiang Zhang; Jue Wang; Na Zuo; Fuqin Sun; Qi Liu; Shaofeng Liu (Functional & Integrative Genomics, 2023)

Altered connectivity in the cognitive control-related prefrontal cortex in Parkinson’s disease with rapid eye movement sleep behavior disorder - Jinjing Liu; Xiaoya Zou; Jinming Gu; Qian Yu; Zhaoying Dong; Hongzhou Zuo; Xiaocui Chen; Xinyi Du; Dezhi Zou; Yu Han; Juan Peng; Oumei Cheng (Brain Imaging and Behavior, 2023)

Improvement of a deterministic fuel management code using artificial neural network for liquid-fueled molten salt reactor - Kaicheng Yu; Maosong Cheng; Xiandi Zuo; Zhimin Dai (Annals of Nuclear Energy, 2023)

Under flooding conditions, controlled-release fertiliser coated microplastics affect the growth and accumulation of cadmium in rice by increasing the fluidity of cadmium and interfering with metabolic pathways - Meng Zhao; Congping Li; Cheng Zhang; Yujie Zhao; Xuexia Wang; Bing Cao; Li Xu; Jiajia Zhang; Jiachen Wang; Qiang Zuo; Yanhua Chen; Guoyuan Zou (Science of The Total Environment, 2023)

Co-pyrolysis of industrial sludge with phytoremediation residue: Improving immobilization of heavy metals at high temperature - Zhiyuan Li; Yaji Huang; Zhicheng Zhu; Mengzhu Yu; Haoqiang Cheng; Hao Shi; Wu Zuo; Haiyun Zhou; Sheng Wang (Fuel, 2023)

In situ growth of polydopamine modified ZIF-L arrays on air-laid paper as flexible evaporator for efficient solar desalination - Long Cheng; Linzhi Zuo; Shitan Yan; Jiubing Shen; Chengping Li; Yiting Che; Liang Wang; Romanov Anton; Ting Bian (Desalination, 2023)

Genome-centric metagenomics provides new insights into metabolic pathways of polyhydroxyalkanoates biosynthesis and functional microorganisms subsisting on municipal organic wastes - Ruo-hong Li; Jin Huang; Cheng-xi Liu; Ke Yu; Feng Guo; You Li; Zuo-hong Chen; Xuan Wang; Ren-xin Zhao; Jia-yu Zhang; Jia-jin Liang; Yun Li; et al. (Water Research, 2023)

Emergence and ecological transition of the Mesozoic marine reptiles: Evidence from the Early Triassic Chaohu and the Middle Triassic Xingyi Faunas - Da-yong Jiang; Min Zhou; Ryosuke Motani; Andrea Tintori; Nicholas C. Fraser; Jian-dong Huang; Olivier Rieppel; Cheng Ji; Wan-lu Fu; Zuo-yu Sun; Hao Lu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Surface fabrication of silica aerogels from inorganic precursor achieving elastic and superhydrophobic sponges for oil-water separation - Xiang Li; Xiaoxiao Huang; Qingge Feng; Zheng Liu; Dongbo Wang; Dachao Ma; Lin Feng; Chen Zuo; Junyi Liu; Sinan Wang; Zhuoyan Huang; Xiaodie Cheng; et al. (Journal of Environmental Chemical Engineering, 2023)

NaNO2 additive-assisted Li2O2 decomposition for highly efficient cathode prelithiation of lithium-ion batteries - Rang Xiao; Cong Kang; Yang Ren; Renlong Li; Jiyuan Jian; Binghan Cui; Geping Yin; Xinqun Cheng; Yulin Ma; Hua Huo; Pengjian Zuo; Guokang Han; et al. (Chemical Engineering Journal, 2023)

Agricultural Vulnerability to Drought in China’s Agro-pastoral Ecotone: A Case Study of Yulin City, Shaanxi Province - Yuheng Li; Wenjing Cheng; Wenjie Zuo; Lingyue Zhang (Chinese Geographical Science, 2023)

Spatio-temporal distribution of organochlorine pesticides in agricultural soils of southeast China during 2014-2019 - Wei Zuo; Qin Lin; Xinju Liu; Lu Lv; Chunrong Zhang; Shenggan Wu; Xi Cheng; Yijun Yu; Tao Tang (Environmental Research, 2023)

Spatial evolution and decomposition of energy-related CO2 emissions in China’s mining industry: from the perspective of regional heterogeneity - Zhili Zuo; Yonglin Li; Haixiang Guo; Jinhua Cheng (Environmental Science and Pollution Research, 2023)

Distribution and Abundance of the East Asian Finless Porpoise in the Coastal Waters of Shandong Peninsula, Yellow Sea, China - Yongtao Li; Zhaolong Cheng; Tao Zuo; Mingxiang Niu; Ruisheng Chen; Jun Wang (Fishes, 2023)
The baseline data pertaining to the population of the East Asian finless porpoise (Neophocaena asiaeorientalis sunameri) in Chinese waters are significantly deficient. Boat-based visual line transect surveys were conducted from 2018 to 2020 to evaluate the distribution and abundance of the East Asian finless porpoise in the coastal waters (depth

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Machine learning improves prediction of severity and outcomes of acute pancreatitis: a prospective multi-center cohort study - Jia-Ning Li; Dong Mu; Shi-Cheng Zheng; Wei Tian; Zuo-Yan Wu; Jie Meng; Rui-Feng Wang; Tian-Lei Zheng; Yue-Lun Zhang; John Windsor; Guo-Tao Lu; Dong Wu (Science China Life Sciences, 2023)

A pansharpening method combining iterative filtering and NSST-NSML-PAPCNN to optimize spatial detail extraction and injection - Jiawen Song; Daming Zhu; Zhitao Fu; Feifei Cheng; Xiaoqing Zuo; Sijing Chen (International Journal of Remote Sensing, 2023)

In-situ advanced oxidation of sediment iron for sulfide control in sewers - Yanchen Liu; Zhiqiang Zuo; He Li; Yaxin Xing; Dong Cheng; Miao Guo; Tao Liu; Min Zheng; Zhiguo Yuan; Xia Huang (Water Research, 2023)

Modularized batch production of 12-inch transition metal dichalcogenides by local element supply - Guodong Xue; Xin Sui; Peng Yin; Ziqi Zhou; Xiuzhen Li; Yang Cheng; Quanlin Guo; Shuai Zhang; Yao Wen; Yonggang Zuo; Chong Zhao; Muhong Wu; et al. (Science Bulletin, 2023)

The decadal abrupt change in the global land vapor pressure deficit - Mengqi Cheng; Zhiyan Zuo; Zouxing Lin; Qinglong You; Huan Wang (Science China Earth Sciences, 2023)

Seismic dynamic stability of double-slider rock slopes containing tension cracks - Chen-hao Zhu; Lian-heng Zhao; Shi-hong Hu; Shi Zuo; Cheng-hao Yu (Journal of Mountain Science, 2023)

The unheeded inherent connections and overlap between microplastics and poly- and perfluoroalkyl substances: A comprehensive review - Peiying Kang; Yaqian Zhao; Chenxin Zuo; Yamei Cai; Cheng Shen; Bin Ji; Ting Wei (Science of The Total Environment, 2023)

Late Quaternary fault activity and deformation mechanism in the eastern Tibet Plateau (Dari fault, Bayan Har Block) - Mingjian Liang; Weiwei Wu; Yao Yang; Fang Du; Wenying Zhou; Hong Zuo; Cheng Liao; Shao Liu; Huiping Zhang (Quaternary International, 2023)

Identification of MYB gene family and functional analysis of GhMYB4 in cotton (Gossypium spp.) - Yuanli Dai; Shang Liu; Dongyun Zuo; Qiaolian Wang; Limin Lv; Youping Zhang; Hailiang Cheng; John Z. Yu; Guoli Song (Molecular Genetics and Genomics, 2023)

Quercetin alleviates tubulointerstitial inflammation by inhibiting exosomes-mediated crosstalk between tubular epithelial cells and macrophages - Di Yin; Jing-Yuan Cao; Yan Yang; Zhong-Tang Li; Hong Liu; Tao-Tao Tang; Wei-Jie Ni; Yi-Lin Zhang; Wei Jiang; Yi Wen; Zuo-Lin Li; Jing Zhao; et al. (Inflammation Research, 2023)

Design, synthesis and mechanism research of novel algicide based on bioactive fragments synthesis strategy - Shi Huang; Lingzi Zuo; Guonian Cheng; Yanlin He; Liexiong Zhang; Qiang Han; Lingling Feng (Pesticide Biochemistry and Physiology, 2023)

Lattice Boltzmann modeling of gaseous microflow in shale nanoporous media - Hong Zuo; Cheng Zhai; Shouchun Deng; Xiaofang Jiang; Farzam Javadpour (Fuel, 2023)

Acid-tailored self-assembled perylene diimide supramolecular for visible-light-driven activation of peroxymonosulfate towards efficient degradation of iohexol - Qiuyi Ji; Kexun Du; Jiandong Zhu; Xiaoqian Ye; Hongjian Li; Xinying Cheng; Yazi Liu; Zhe Xu; Gancheng Zuo; Shiyin Li; Shaogui Yang; Limin Zhang; et al. (Chemical Engineering Journal, 2023)

Crystal structural analysis and characterization for MlrC enzyme of Sphingomonas sp. ACM-3962 involved in linearized microcystin degradation - Xiaoliang Guo; Qinqin Jiang; Zengru Li; Cai Cheng; Yu Feng; Yanlin He; Lingzi Zuo; Wei Ding; Delin Zhang; Lingling Feng (Chemosphere, 2023)

Evaluation of production capacity for rice-rapeseed cropping system in China - Jiada Huang; Xinyuan Cao; Jie Kuai; Hui Cheng; Qingsong Zuo; Hai Du; Shaobing Peng; Jianliang Huang; Nanyan Deng (Field Crops Research, 2023)

Exploring the heterogeneity in drivers of energy-saving behaviours among hotel guests: Insights from the theory of planned behaviour and personality profiles - Qian-Cheng Wang; Yi-Tian Ren; Xuan Liu; Rui-Dong Chang; Jian Zuo (Environmental Impact Assessment Review, 2023)

IiSVP of Isatis indigotica can reduce the size and repress the development of floral organs - Qi Meng; Xiao-Fang Hou; Hao Cheng; Xiao-Min Tan; Zuo-Qian Pu; Zi-Qin Xu (Plant Cell Reports, 2023)

Superhydrophobic copper foam bed with extended permeation channels for water-in-oil emulsion separation with high efficiency and flux - Zehao Chen; Jihao Zuo; Ting Zhao; Qing Tan; Yunjun Nong; Shouping Xu; Jiang Cheng; Xiufang Wen; Pihui Pi (Journal of Environmental Chemical Engineering, 2023)

Br-doping mediated band-gap engineering contributed Bi/Bi2O2CO3 nano-platelets with enhanced photocatalytic performance - Chenyu Wu; Huiru Zuo; Shengjie Zhao; Yanan Cheng; Zhiyuan Guo; Qishe Yan (Chemical Engineering Journal, 2023)

Adjustment for the Age- and Gender-Related Metabolic Changes Improves the Differential Diagnosis of Parkinsonism - Jiaying Lu; Min Wang; Ping Wu; Igor Yakushev; Huiwei Zhang; Sibylle Ziegler; Jiehui Jiang; Stefan Förster; Jian Wang; Markus Schwaiger; Axel Rominger; Sung-Cheng Huang; et al. (Phenomics, 2023)

Towards a decoupling between regional economic growth and CO2 emissions in China's mining industry: A comprehensive decomposition framework - Yonglin Li; Zhili Zuo; Yue Cheng; Jinhua Cheng; Deyi Xu (Resources Policy, 2023)

Developing a UV dosing strategy for UV/chlorine process towards the trade-off between pharmaceuticals and personal care products degradation and disinfection by-products formation - Shi Cheng; Yanting Zuo; Aimin Li; Haohan Jiang; Wenliang Ji; Ji Wu; Wentao Li; Zhe Wang; Yonglin Zhou; Feng Zhu; Wei He; Zongli Huo; et al. (Journal of Cleaner Production, 2023)

Sand-fixing effect and compound change of nylon checkerboard sand barrier - Cheng Xi; Hejun Zuo; Xianghong Wei; Min Yan (Environmental Science and Pollution Research, 2022)

46,XY disorders of sex development: the use of NGS for prevalent variants - Qi-Gen Xie; Peng Luo; Kai Xia; Zuo-Qing Li; Zhe Xu; Cheng Su; Chun-Hua Deng (Human Genetics, 2022)

Huge sedimentary hiatus in the southern margin of the North China Craton from mid-Mesoproterozoic to Neoproterozoic - Pengfei Zuo; Yu Li; Haihua Cheng; Christopher J. Spencer; Fengbo Sun; Shiyan Wang; Deshun Zheng (International Geology Review, 2022)

The distinct disrupted plasticity in structural and functional network in mild stroke with basal ganglia region infarcts - Hua Zhu; Lijun Zuo; Wanlin Zhu; Jing Jing; Zhe Zhang; Lingling Ding; Fengjuan Wang; Jian Cheng; Zhenzhou Wu; Yongjun Wang; Tao Liu; Zixiao Li (Brain Imaging and Behavior, 2022)

Ice-Water-Gas Interaction during Icebreaking by an Airgun Bubble - Qi-Gang Wu; Zuo-Cheng Wang; Bao-Yu Ni; Guang-Yu Yuan; Yuriy A. Semenov; Zhi-Yuan Li; Yan-Zhuo Xue (Journal of Marine Science and Engineering, 2022)
When an airgun releases high-pressure gas underwater below an ice plate, it is observed that a bubble is formed rapidly while the ice plate is broken fiercely. In order to study the ice-water-gas interaction during this transient and violent phenomenon, a set of laboratory-scale devices was designed and a series of icebreaking experiments were carried out. High-speed photography was used to capture the evolution of the bubble and the ice plate. It was found that the airgun bubble had a unique ‘pear’ shape compared with the spherical bubble generated by electric sparking. The pressure induced by the pulsation of the airgun bubble near a rigid wall was measured by the pressure sensor. The initial shockwave, oscillatory pressure peaks caused by the directional fast air injection, secondary shockwave, and pressure peak caused by the bubble jet impact were clearly recorded. Three damage patterns of ice plates were observed and corresponding reasons were analyzed. The influence of dimensionless parameters, such as airgun-ice distance H and ice thickness T, was also investigated. The physical mechanism of ice-water-gas interaction was summarized.

Comprehensive Analysis of Aldehyde Dehydrogenases (ALDHs) and Its Significant Role in Hepatocellular Carcinoma - Senbang Yao; Wenjun Chen; He Zuo; Ziran Bi; Xiuqing Zhang; Lulian Pang; Yanyan Jing; Xiangxiang Yin; Huaidong Cheng (Biochemical Genetics, 2022)
Oxidative DNA damage is closely related to the occurrence and progression of cancer. Oxidative stress plays an important role in alcohol-induced hepatocellular carcinoma (HCC). Aldehyde dehydrogenase (ALDH) is a family of enzymes that plays an essential role in the reducing oxidative damage. However, how ALDHs family affects alcohol-related HCC remains obscure. We aimed to explore the correlation between the differential expression of ALDHs in patients with HCC and pathological features, as well as the relationship between ALDHs and prognosis, and finally analyze the possible mechanism of ALDHs in targeted therapy of HCC. The data of HCC were downloaded from The Cancer Genome Atlas (TCGA) database. This research explored the expression and prognostic values of ALDHs in HCC using Oncomine, UALCAN, Human Protein Atlas, cBioPortal, Kaplan–Meier plotter, GeneMANIA, Tumor Immune Estimation Resource, GEPIA databases, and WebGestalt. Low mRNA and protein expressions of ALDHs were found to be significantly associated with tumor grade and clinical cancer stages in HCC patients. In particular, the loss of ALDH expression is more obvious in Asians, and its effect on prognosis is far more significant than that in the White race. Our findings play an important role in the study of prognostic markers and anti-liver cancer therapeutic targets for the members of the ALDHs family, especially in patients with liver cancer in Asia.

Effects of micronized bamboo powder on growth performance, serum biochemical indexes, cecal chyme microflora and metabolism of broilers aged 1–22 days - Fawen Dai; Tao Lin; Lumin Cheng; Jian Wang; Jianjun Zuo; Dingyuan Feng (Tropical Animal Health and Production, 2022)
Adding insoluble fiber to diet of broilers has been reported to improve intestinal health and promote growth performance. Bamboo powder is a cheap raw material with rich insoluble fiber. This study aims to explore the effects of feeding micronized bamboo powder (MBP) on growth performance, serum biochemical indexes, intestinal microflora, and metabolism of broilers. A total of 1440 1-day-old slow-growing Ephedra chickens were randomly divided into three groups considering gender and body weight: (1) Group D: feeding with basal diet without antibiotics; (2) Group E: feeding with basal diet supplemented with 5% rice bran (RB); (3) Group F: feeding with basal diet supplemented with 1% MBP. Each group involved 8 replicates feeding for 22 days, with 60 chickens per replicate. Various indexes were detected. For the growth performance, the weight gain and feed consumption ratio (G: F) of Group F supplemented with MBP is 0.57 ± 0.04, which is significantly higher than that of E group supplemented with RB (0.52 ± 0.01, P < 0.05). For the serum biochemical indexes, the glutathione peroxidase activity in Group F is significantly higher than that of Group D, while the malondialdehyde content is significantly lower than that of Group D and Group E ( P < 0.05 for all). The fresh cecal chyme is taken for determination. In Group F, the α diversity index Faith_pd is significantly lower in Group F than that of Group D. The microorganism species in cecal chyme of Group F and Group E are also different. The metabolic pathways of Group F, mainly in fatty acid metabolism, amino acid metabolism and intestinal immune IgA production, were different from those of Group D and Group E. Adding 1% MBP to broiler diet can enhance the anti-oxidant capacity, improve chyme microflora, regulate the metabolism pathways responsible for intestinal fatty acids, amino acids, and immunity.

Novel bioavailability-based risk assessment of Cd in earthworms and leeches utilizing in vitro digestion/Caco-2 and MDCK cells - Tian-tian Zuo; Fei-ya Luo; Huai-zhen He; Hong-yu Jin; Lei Sun; Shu-xia Xing; Bo Li; Fei Gao; Shuang-cheng Ma; Lang-chong He (Environmental Science and Pollution Research, 2022)

Petrogenesis and tectonic setting of the early-middle triassic subduction-related granite in the eastern segment of East Kunlun: evidences from petrology, geochemistry, and zircon U-Pb-Hf isotopes - Zuo-Chen Li; Xian-Zhi Pei; Paul D. Bons; Rui-Bao Li; Lei Pei; Guo-Chao Chen; You-Xin Chen; Cheng-Jun Liu; Meng Wang; Shao-Wei Zhao; Xiao-Bing Li; Feng Gao (International Geology Review, 2022)

Disrupted functional connectivity in white matter resting-state networks in unilateral temporal lobe epilepsy - Xuan Li; Yuchao Jiang; Wei Li; Yingjie Qin; Zhiliang Li; Yan Chen; Xin Tong; Fenglai Xiao; Xiaojun Zuo; Qiyong Gong; Dong Zhou; Dezhong Yao; et al. (Brain Imaging and Behavior, 2022)

Genome-wide identification and expression analysis of GL2-interacting-repressor (GIR) genes during cotton fiber and fuzz development - Xiaoxu Feng; Hailiang Cheng; Dongyun Zuo; Youping Zhang; Qiaolian Wang; Limin Lv; Shuyan Li; John Z. Yu; Guoli Song (Planta, 2022)

Functional connectivity patterns of the subgenual anterior cingulate cortex in first-episode refractory major depressive disorder - Bochao Cheng; Yajing Meng; Yan Zuo; Yi Guo; Xiuli Wang; Song Wang; Ran Zhang; Wei Deng; Yingkun Guo; Gang Ning (Brain Imaging and Behavior, 2021)

Preface to the Special Issue on Digital Geosciences and Quantitative Exploration of Mineral Resources - Qiuming Cheng; Yongqing Chen; Renguang Zuo (Journal of Earth Science, 2021)

Sustained effects of one-time sewage sludge addition on rice yield and heavy metals accumulation in salt-affected mudflat soil - Wengang Zuo; Yanchao Bai; Ming Lv; Zehui Tang; Cheng Ding; Chuanhui Gu; Yuhua Shan; Qigen Dai; Min Li (Environmental Science and Pollution Research, 2021)

Ecological Security Assessment of the G20 and its Drivers: EF-Path-STIRPAT Modeling - Zhili Zuo; Haixiang Guo; Jinhua Cheng; Shicheng Li (Natural Resources Research, 2020)

Geographical origin differentiation of Chinese Angelica by specific metal element fingerprinting and risk assessment - Lei Sun; Xiao Ma; Hong-Yu Jin; Chang-jun Fan; Xiao-dong Li; Tian-Tian Zuo; Shuang-Cheng Ma; Sicen Wang (Environmental Science and Pollution Research, 2020)

Outflow sediment concentration forecasting by integrating machine learning approaches and time series analysis in reservoir desilting operation - Ming-Jui Chang; Gwo-Fong Lin; Fong-Zuo Lee; Yi-Cheng Wang; Peng-An Chen; Ming-Chang Wu; Jihn-Sung Lai (Stochastic Environmental Research and Risk Assessment, 2020)

Innovative health risk assessments of heavy metals based on bioaccessibility due to the consumption of traditional animal medicines - Tian-Tian Zuo; Hao-Ran Qu; Hong-Yu Jin; Lei Zhang; Fei-Ya Luo; Kun-Zi Yu; Fei Gao; Qi Wang; Lei Sun; Huai-Zhen He; Shuang-Cheng Ma (Environmental Science and Pollution Research, 2020)

HOXB13 expression is correlated with hepatic inflammatory activity of patients with hepatic fibrosis - Lingyun Zuo; Tingting Tan; Cheng Wei; Huali Wang; Luxuan Tan; Yingying Hao; Jingjing Qian; Yuxin Chen; Chao Wu (Journal of Molecular Histology, 2020)

A new statistical method for detecting trend turning - Bin Zuo; Jianping Li; Cheng Sun; Xin Zhou (Theoretical and Applied Climatology, 2019)

Numerical Simulation and Analysis of Surface and Surrounding Rock Failure in Deep High-Dip Coal Seam Mining - Qian Cheng; Yongkui Shi; Lingqun Zuo (Geotechnical and Geological Engineering, 2019)

Reduced Systemic and Brain Exposure with Inhibited Liver Metabolism of Carbamazepine After Its Long-Term Combination Treatment with Piperine for Epilepsy Control in Rats - Tianjing Ren; Min Xiao; Mengbi Yang; Jiajia Zhao; Yufeng Zhang; Mengyun Hu; Yan Cheng; Hong Xu; Chunbo Zhang; Xiaoyu Yan; Zhong Zuo (The AAPS Journal, 2019)

Correction to: Fine mapping and identification of the fuzzless gene GaFzl in DPL972 (Gossypium arboreum) - Xiaoxu Feng; Hailiang Cheng; Dongyun Zuo; Youping Zhang; Qiaolian Wang; Ke Liu; Javaria Ashraf; Qiuhong Yang; Simin Li; Xiaoqin Chen; Guoli Song (Theoretical and Applied Genetics, 2019)

Fine mapping and identification of the fuzzless gene GaFzl in DPL972 (Gossypium arboreum) - Xiaoxu Feng; Hailiang Cheng; Dongyun Zuo; Youping Zhang; Qiaolian Wang; Ke Liu; Javaria Ashraf; Qiuhong Yang; Simin Li; Xiaoqin Chen; Guoli Song (Theoretical and Applied Genetics, 2019)

Characteristics of failure area and failure mechanism of a bedding rockslide in Libo County, Guizhou, China - Lianheng Zhao; Dejian Li; Hanhua Tan; Xiao Cheng; Shi Zuo (Landslides, 2019)

Seabed deposition and erosion change and influence factors in the Yangshan Deepwater Port over the years - Shuhua Zuo; Hualiang Xie; Xiaoming Ying; Cheng Cui; Yuxin Huang; Huaiyuan Li; Mingxiao Xie (Acta Oceanologica Sinica, 2019)

Refined assessment of heavy metal-associated health risk due to the consumption of traditional animal medicines in humans - Tian-Tian Zuo; Yao-Lei Li; Huai-Zhen He; Hong-Yu Jin; Lei Zhang; Lei Sun; Fei Gao; Qi Wang; Yuan-Jun Shen; Shuang-Cheng Ma; Lang-Chong He (Environmental Monitoring and Assessment, 2019)

Analyzing Influencing Factors of Rural Poverty in Typical Poverty Areas of Hainan Province: A Case Study of Lingao County - Jinping Zhang; Feng Zuo; Yanmei Zhou; Mengxiao Zhai; Lin Mei; Yidi Fu; Yeqing Cheng (Chinese Geographical Science, 2018)

Adsorption and mineralization of REE—lanthanum onto bacterial cell surface - Yangjian Cheng; Li Zhang; Xiaojing Bian; Hongyang Zuo; Hailiang Dong (Environmental Science and Pollution Research, 2018)

The Earth's natural pulse electromagnetic fields for earthquake time–frequency characteristics: Insights from the EEMD–WVD method - Guo‐Cheng Hao; Yu‐Xiao Bai; Hui Liu; Juan Zhao; Zuo‐Xun Zeng (Island Arc, 2018)
Monitoring the Earth's natural pulse electromagnetic field (ENPEMF) signal is a geomagnetic detection approach for the Earth internal and external studies, and it provides a reference for earthquake prediction. In this paper, the Ensemble Empirical Mode Decomposition–Wigner Ville Distribution (EEMD–WVD) method is used to process the time sequences of the ENPEMF signal detected by GR‐01 receiving devices during the Lushan M S 7.0 earthquake (April 20th, 2013). By obtaining the intrinsic mode function (IMF), the time–frequency–amplitude joint distribution and the energy spectrum of the ENPEMF signal, the suspected anomalies before the earthquake could be shown. The results illustrate the ENPEMF signal before an earthquake and its time–frequency characteristics based on an EEMD–WVD algorithm, proving useful information about the anomalies around the time of the earthquake.

Fate of antibiotic and metal resistance genes during two-phase anaerobic digestion of residue sludge revealed by metagenomic approach - Ying Wu; Erping Cui; Yiru Zuo; Weixiao Cheng; Hong Chen (Environmental Science and Pollution Research, 2018)

Roles of flotillins in tumors - Xu-xu Liu; Wei-dong Liu; Lei Wang; Bin Zhu; Xiao Shi; Zi-xuan Peng; He-cheng Zhu; Xing-dong Liu; Mei-zuo Zhong; Dan Xie; Mu-sheng Zeng; Cai-ping Ren (Journal of Zhejiang University-SCIENCE B, 2018)

Mapping spatial distribution characteristics of lineaments extracted from remote sensing image using fractal and multifractal models - Cheng Lyu; Qiuming Cheng; Renguang Zuo; Xueping Wang (Journal of Earth Science, 2017)

Complete genome sequence of Menghai flavivirus, a novel insect-specific flavivirus from China - Xianglilan Zhang; Xiaofang Guo; Hang Fan; Qiumin Zhao; Shuqing Zuo; Qiang Sun; Guangqian Pei; Shi Cheng; Xiaoping An; Yunfei Wang; Zhiqiang Mi; Yong Huang; et al. (Archives of Virology, 2017)

Occurrence and photodegradation of methylmercury in surface water of Wen-Rui-Tang River network, Wenzhou, China - Shuihong Pan; Chuchu Feng; Jialu Lin; Lidong Cheng; Chengjun Wang; Yuegang Zuo (Environmental Science and Pollution Research, 2017)

Complete genome sequence of Menghai rhabdovirus, a novel mosquito-borne rhabdovirus from China - Qiang Sun; Qiumin Zhao; Xiaoping An; Xiaofang Guo; Shuqing Zuo; Xianglilan Zhang; Guangqian Pei; Wenli Liu; Shi Cheng; Yunfei Wang; Peng Shu; Zhiqiang Mi; et al. (Archives of Virology, 2017)

Rice grassy stunt virus nonstructural protein p5 serves as a viral suppressor of RNA silencing and interacts with nonstructural protein p3 - Chao Zhang; Xiao-juan Liu; Kang-cheng Wu; Lu-Ping Zheng; Zuo-mei Ding; Fei Li; Peng Zou; Liang Yang; Jian-guo Wu; Zu-jian Wu (Archives of Virology, 2015)

Liver transplantation nearly normalizes brain spontaneous activity and cognitive function at 1 month: a resting-state functional MRI study - Yue Cheng; Lixiang Huang; Xiaodong Zhang; Jianhui Zhong; Qian Ji; Shuangshuang Xie; Lihua Chen; Panli Zuo; Long Jiang Zhang; Wen Shen (Metabolic Brain Disease, 2015)

Schwann cells induce Proliferation and Migration of Oligodendrocyte Precursor Cells Through Secretion of PDGF-AA and FGF-2 - Yue-Juan Chen; Jing-Xing Zhang; Lin Shen; Qi Qi; Xiao-Xin Cheng; Zheng-Rong Zhong; Zhi-Quan Jiang; Rui Wang; He-Zuo Lü; Jian-Guo Hu (Journal of Molecular Neuroscience, 2015)

The mineralization age of the Makeng Fe deposit, South China: implications from U–Pb and Sm–Nd geochronology - Zhenjie Zhang; Renguang Zuo; Qiuming Cheng (International Journal of Earth Sciences, 2015)

Genetic diversity and evolution of two capsid protein genes of citrus tristeza virus isolates from China - Guan-Wei Wu; Min Tang; Guo-Ping Wang; Feng-Yin Jin; Zuo-Kun Yang; Li-Jing Cheng; Ni Hong (Archives of Virology, 2015)

Conjugated linoleic acid alters growth performance, tissue lipid deposition, and fatty acid composition of darkbarbel catfish (Pelteobagrus vachelli) - Gui-Fang Dong; Wen-Zuo Liu; Lin-Zhou Wu; Deng-hang Yu; Feng Huang; Peng-Cheng Li; Yan-ou Yang (Fish Physiology and Biochemistry, 2015)

Effects of Tirofiban on Platelet Activation and Endothelial Function in Patients with ST-Elevation Myocardial Infarction Undergoing Primary Percutaneous Coronary Intervention - Kuan Wang; Guoxing Zuo; Liuying Zheng; Cheng Zhang; Dong Wang; Zhongnan Cao; Sheng Hu; Xinping Du (Cell Biochemistry and Biophysics, 2015)

Evaluation of the formation of volatiles and sensory characteristics of persimmon ( Diospyros kaki L.f.) fruit wines using different commercial yeast strains of Saccharomyces cerevisiae - Jian Cai Zhu; Yun Wei Niu; Tao Feng; Sheng Jiang Liu; He Xing Cheng; Na Xu; Hai Yan Yu; Zuo Bing Xiao (Natural Product Research, 2014)

Response to comment by Helmut Schaeben on “A Comparison of Modified Fuzzy Weights of Evidence, Fuzzy Weights of Evidence, and Logistic Regression for Mapping Mineral Prospectivity” - Daojun Zhang; Frits Agterberg; Qiuming Cheng; Renguang Zuo (Mathematical Geosciences, 2014)

A Comparison of Modified Fuzzy Weights of Evidence, Fuzzy Weights of Evidence, and Logistic Regression for Mapping Mineral Prospectivity - Daojun Zhang; Frits Agterberg; Qiuming Cheng; Renguang Zuo (Mathematical Geosciences, 2014)

The comparison of sensitivity of motion sickness between retinal degeneration fast mice and normal mice - Xiao-Cheng Wang; Zhao-Hui Shi; Ka Bian; Lei Zhang; Jun-Hui Xue; Guo-Qing Yang; Xue-Song Ge; Zuo-Ming Zhang (Journal of Comparative Physiology A, 2014)

Combined effect of five single nucleotide polymorphisms related to IL23/Th17 pathway in the risk of psoriasis - Xianyong Yin; Hui Cheng; Ran Zhang; Xing Fan; Fusheng Zhou; Long Jiang; Xianfa Tang; Gang Chen; Xianbo Zuo; Xiaodong Zheng; Sen Yang; Xuejun Zhang (Immunogenetics, 2014)

Cyclic AMP-Dependent Protein Kinase Enhances SC35-Promoted Tau Exon 10 Inclusion - Caoyi Chen; Nana Jin; Wei Qian; Wen Liu; Xiangling Tan; Fei Ding; Xiaosong Gu; Khalid Iqbal; Cheng-Xin Gong; Ji Zuo; Fei Liu (Molecular Neurobiology, 2014)

The association between a single nucleotide polymorphism rs11966200 in MHC region and clinical features of generalized vitiligo in Chinese Han population - Jin Tang; Jian Lan Liu; Cheng Zhang; Da Yan Hu; Su Min He; Xian Bo Zuo; Pei Guang Wang; Liang Dan Sun; Xue Jun Zhang; Sen Yang (Molecular Biology Reports, 2013)

Sesamin extends the mean lifespan of fruit flies - Yuanyuan Zuo; Cheng Peng; Yintong Liang; Ka Ying Ma; Ho Yin Edwin Chan; Yu Huang; Zhen-Yu Chen (Biogerontology, 2013)

Diffusion magnetic resonance imaging for Brainnetome: A critical review - Nianming Zuo; Jian Cheng; Tianzi Jiang (Neuroscience Bulletin, 2012)

Atmospheric scattering and turbulence modulation transfer function for CCD cameras on CBERS-02b and HJ-1A/1B - Xiaoying Li; Xingfa Gu; Tao Yu; Tianhai Cheng; Jiaguo Li; Hailiang Gao; Zuo Wang (International Journal of Remote Sensing, 2012)

Prevalence and Isoforms of the Pathogenicity Island ETT2 Among Escherichia coli Isolates from Colibacillosis in Pigs and Mastitis in Cows - DaRong Cheng; ShanYuan Zhu; ZhiRui Su; WeiYong Zuo; Hui Lu (Current Microbiology, 2012)

Magnetostratigraphic dating of the Hougou Paleolithic site in the Nihewan Basin, North China - TianWen Zuo; HongJiang Cheng; Ping Liu; Fei Xie; ChengLong Deng (Science China Earth Sciences, 2011)

Assessment of the role of brine shrimp Artemia in white spot syndrome virus (WSSV) transmission - Jia-Song Zhang; Shuang-Lin Dong; Yun-Wei Dong; Xiang-Li Tian; Yi-Cheng Cao; Zuo-Jia Li; Dong-Chun Yan (Veterinary Research Communications, 2010)

A “GC-rich” method for mammalian gene expression: A dominant role of non-coding DNA GC content in regulation of mammalian gene expression - Qian Jia; HongTao Wu; XingJun Zhou; Jian Gao; Wei Zhao; JouDi Aziz; JingShuang Wei; Lihua Hou; Shuyin Wu; Ying Zhang; XiangFeng Dong; YanMin Huang; et al. (Science China Life Sciences, 2010)

Phylogenetic analysis of Mycoplasma suis isolates based on 16S rRNA gene sequence in China - Rong-Qiong Zhou; Kui Nie; Han-Cheng Huang; Shi-jun Hu; Zuo-yong Zhou; Hong-Lin Luo (Veterinary Research Communications, 2009)

Establishment and characterization of a new highly metastatic human osteosarcoma cell line - Yuxi Su; Xiaoji Luo; Bai-Cheng He; Yi Wang; Liang Chen; Guo-Wei Zuo; Bo Liu; Yang Bi; Jiayi Huang; Gao-Hui Zhu; Yun He; Quan Kang; et al. (Clinical & Experimental Metastasis, 2009)

Effects of phytase pretreatment of soybean meal and phytase-sprayed in diets on growth, apparent digestibility coefficient and nutrient excretion of rainbow trout (Oncorhynchus mykiss Walbaum) - Feng Wang; Yu-Hong Yang; Zhi-Zhong Han; Hong-Wei Dong; Cheng-Hui Yang; Zuo-Yu Zou (Aquaculture International, 2009)

Application of Fractal Models to Distinguish between Different Mineral Phases - Renguang Zuo; Qiuming Cheng; Qinglin Xia; F. P. Agterberg (Mathematical Geosciences, 2009)

A view‐dependent method for the multi‐resolution representation of terrains with roads embedded - X. Zuo; Q. Li; B. Yang; T. Cheng (International Journal of Remote Sensing, 2007)

GSTP1 polymorphisms and gastric cancer in a high-risk Chinese population - Veronica Wendy Setiawan; Zuo-Feng Zhang; Guo-Pei Yu; Qing-Yi Lu; Yong-Liang Li; Ming-Lan Lu; Ming-Rong Wang; Chun Hua Guo; Shun-Zhang Yu; Robert C Kurtz; Chung-Cheng Hsieh (Cancer Causes & Control, 2001)